Enhanced Colorectal Surgery Bundle to Reduce Surgical Site Infections. (4th October 2017) - Ghanem, Angie; Hall, Stephanie; Cologne, Kyle; Nanda, Neha
Abstract: Background: In 2015, we observed 59% more colon surgery SSIs than predicted by National Healthcare Surveillance Network (NHSN) national data at a large university-based hospital in Los Angeles, CA. This translated to a 63% increase from 2014 in the complex 30-day Center for Medicare and Medicaid Services (CMS) standardized infection ratio (SIR). In order to enhance our colon SSI prevention program, we created a bundle to implement best practices to standardize procedures among surgeons. The goal was to reduce the CMS SIR by 10% by the end of the calendar year. Methods: A multi-disciplinary team was formed to develop a colon surgery SSI reduction bundle which incorporated established SSI prevention strategies as well as a procedure for fascia closure which included changing gloves, removal of all dirty instruments, and use of a dedicated instrument tray for closure. All process measures were monitored through chart review and SSIs were determined by Infection Prevention. Monthly meetings with team members were held and feedback given to surgeons. Results: The major elements of the bundle were implemented first among colorectal surgery and then among other services that also perform colon surgery. Throughout 3 quarters of monitoring, the average compliance with glove change was 79% among all surgical services and 86% among colorectal surgery. The average compliance with the dedicated closure tray was 69% among all surgical services and 74% among colorectal surgery. Despite a lower compliance than expected for process measures, we observed a 54% decrease in the CMS SIR from 2015 to 2016 (from 14 deep and organ/space infections to 9). Conclusion: We observed a reduction in SSIs after implementing a bundle with key process measures. Data abstraction was limited by relying on chart documentation, however, it has indicated continued opportunities for surgeon engagement and collaboration with OR staff. Next steps include continued awareness regarding bundle components and implementation of additional phases- peri-operative and post-operative care. Disclosures: All authors: No reported disclosures.